Cloud Architecture and Certification Jump Start - Sequeira, Anthony (Addison-Wesley Professional, 2020)
4.5+ Hours of Video Instruction Description The Cloud Technology and Certifications Jump Start video course covers critical information about cloud technologies, including the "Big Four" public cloud vendors, and their offerings. This course also covers such practical guidance as how to plan a migration to the cloud and the tools available for migration. Overview The goal of Cloud Technology and Certifications Jump Start Livelessons clarifies why cloud technologies are revolutionizing and dominating the IT industry and provides the basics you need to start your cloud career. By providing many real-world examples to illustrate the sea changes taking place, and walking through the various options available, this course explains the benefits of cloud computing. This video series also provides very practical information about each of the Big Four public cloud vendors. This provides the learner with an understanding of the offerings of each of these major players in the industry and also permits a student to see the trends that are occurring in the space as they compare the offerings from the dominant players. The course starts with the evolution of cloud computing, the types of deployments, and the steps to deploy technologies today. The course also covers such important topics as cloud security, cloud migrations, and the architectural design changes that make your solutions much more "cloud-ready". Lastly, the course provides an overview of the various certifications offered by the Big Four cloud vendors. Topics include: The Evolution of Cloud Computing The Big Four Public Cloud Vendors Adopting Cloud Technologies Cloud Migrations Cloud Certifications About the Instructor Anthony Sequeira, CCIE No. 15626, is a seasoned trainer and author regarding various levels and tracks of Cisco, Microsoft, and AWS certifications. Anthony formally began his career in the information technology industry in 1994 with IBM in Tampa, Florida. He quickly formed his own computer consultancy, Computer Solutions, and then discovered his true passion'Äîteaching and writing about information technologies. Anthony joined Mastering Computers in 1996 and lectured to massive audiences around the world about the latest in computer technologies. Mastering Computers became the revolutionary online training company KnowledgeNet, and Anthony trained there for many years. Anthony is currently pursuing his second CCIE in the area of Cisco Data Center! Anthony is currently a freela...
Online resource; Title from title screen (viewed June 19, 2020)
Keywords: Electronic videos